The Effectiveness of Distance Education in Light Of Technological Advancements (مجلة إحالات, 2026)
This research addressed the effectiveness of distance education in light of technologicaladvancements, with a focus on the "Moodle" platform as a leading educational tool in achieving sucheffectiveness. The study highlighted the importance of distance education in providing flexible andinteractive learning environments, benefiting from digital developments to overcome the constraintsof time and space. Special attention was given to the role of Moodle as an open-source electroniclearning environment that supports both self-directed and collaborative learning through assessmenttools, course management, and enhanced interaction between teachers and learners. The resultsshowed that utilizing Moodle contributes to improving academic achievement and developing learners' self-directed skills, provided that good planning and proper training on using the platform are ensured. The research concluded by emphasizing the importance of integrating modern interactive platforms to sustain the effectiveness of distance education and improve its outcomes.